Philippines : Meeting the Infrastructure Challenges - World Bank (Washington, DC, 2012)
The Philippines enjoys tremendous endowments of natural, and human resources that provide great potential for economic development and poverty reduction. However, overall development outcomes over the last decades have fallen short of potential. The gap can be largely attributed to weak performance of public institutions in providing services to citizens, which leads to a vicious cycle of weak public services, lack of trust in the government, and unwillingness on the part of citizens to provide adequate resources to the government. The key development challenge, therefore, is to reverse the cycle to one of virtuous development where increased government revenue translates into improved service delivery and greater public trust in the government. Infrastructure plays an important role in this development process. Insufficient infrastructure has been a major constraint to economic growth and poverty reduction in the Philippines. Though the country has relatively high access levels to water, sanitation, and electricity, service levels have failed to keep up with rapid population growth and urbanization. Infrastructure development in the country is hampered by a poor business environment; weaknesses in planning, coordination, and financing; and a decrease in private sector involvement in infrastructure provision. The report presents a road map which will help spur the expansion, and improvement of infrastructure services, and move the country into a virtuous circle of growth and development. It suggests that, in order to ease infrastructure constraints, the Philippines need to achieve a gradual increase in infrastructure investments to at least 5 percent of GDP, and an increase in the efficiency of spending. Furthermore, it is strongly suggested that the way forward for sustained development in infrastructure requires instigating a rigorous fiscal reform program; pursuing continued reforms in key sectors-particularly power, roads, and water-to improve cost recovery, competition, and institutional credibility, and to sharply reduce corruption; improving central oversight of the planning and coordination of investments; and, making a few focused investments through public-private partnerships to address key bottlenecks, and achieve quick gains in service delivery.